FARMERS’ PREFERENCES FOR SELECTED ATTRIBUTES OF POTATO IN EAST KHASI DISTRICT OF MEGHALAYA - Sah, Uma; Kumar, Shantanu; Deka, C. K.; Pandey, N. K (Potato Journal, 2013)
The study was conducted in the year 2002-2003 in east Khasi hill district of Meghalaya state. Potato was the most preferred crop among majority of the respondents. Short duration, good storability of the harvest combined with good level of production were the reasons cited by more than 72 percent potato farmers for preferring potato crop. Cv. Kufri Jyoti was the most preferred cultivar. Among the six major attributes, disease resistance was ranked as the most important attribute in improved cultivars, followed by higher yield and sustainability of yield. Better keeping quality followed by short duration of maturity were perceived as least important attributes.